Optimasi Tata Letak Gudang Interior PT. XYZ melalui Penerapan Class Based Storage dengan Klasifikasi ABC - Yunianto, Moreno; Rudi Tjahyono (Jurnal Serambi Engineering, 2026)
The interior warehouse at PT. XYZ, a bus body manufacturing company, experiences operational inefficiencies due to the implementation of a Dedicated Storage system. This system leads to non-optimal picking times and long travel distances for operators, especially during peak activity periods (rush hour), because high-movement items are not strategically placed near the Input/Output (I/O) point. This research aims to optimize the warehouse layout by implementing the Class-Based Storage method based on ABC classification. Data on item movement (inbound and outbound) over 12 weeks were collected and analyzed. The ABC analysis categorized items into three classes: A (fast-moving), B (medium-moving), and C (slow-moving). The results show that four items (Snap ring outer, Masking Tape, Karet O-ring, and Transition Board) belong to Class A, contributing to 74% of the total movement frequency. The proposed layout places Class A items closest to the I/O point, Class B in the middle area, and Class C on the second floor. This systematic reorganization is expected to significantly reduce picking time and travel distance, improve space utilization, and ultimately enhance overall warehouse productivity and support smoother production operations at PT. XYZ.